Riders to the Sea de Ralph Vaughan Williams : un hymne à la mer, indomptable et indomptée, qui unit les nations - Florence Le Doussal (Revue LISA)
Riders to the Sea: An opera in one act based on the play by John Millington Synge, Ralph Vaughan Williams’s fifth opera, composed between 1925 and 1932, after The Poisoned Kiss (A Romantic Extravaganza), was first performed at London’s Royal College of Music on December 1st, 1937, with Malcolm Sargent conducting. A masterpiece of poetic intensity and a compendium of pain and quiet, resigned courage, worthy of a Greek tragedy, the Irish dramatist’s play was faithfully adapted by the composer-librettist in a work whose originality and universal message cannot fail to impress. Originating in his wide-ranging imagination―humanistic, brotherly, idealistic, universal―it speaks of a voyage of initiation to the Aran Islands, off the west coast of Ireland. The composer, inspired by folk wisdom and the world of the Spirit, open to worldly solicitations as well as to meditation, saw the play as a vehicle to highlight some aspects of his own musical heritage. In a few pages of dialogue, the score conveys a whole range of different emotions arising from the confrontation with Nature, and more particularly, from the forlorn struggle of the islanders against the sea and God, their ruler.